The smart cookie eaudiobook - John, Jory (The Food Group, 2021)
An Instant New York Times Bestseller! Be a smart cookie—and don't miss the fifth picture book in the #1 New York Times bestselling Food Group series from creators Jory John and Pete Oswald! This cookie has never felt like a smart cookie no matter how hard she tries, especially in comparison to all the clever cupcakes and brilliant rolls in the bakery. Will a dash of creativity and a sprinkle of confidence be enough to help her learn that perfect scores and having all the answers aren't the only ingredients for intelligence? Jory John and Pete Oswald serve up another heaping plate of laughs and lessons with this empowering, witty, and charming addition to their #1 New York Times bestselling series! Check out Jory John and Pete Oswald's funny, bestselling books for kids 4-8 and anyone who wants a laugh: The Bad Seed The Good Egg The Cool Bean The Couch Potato The Good Egg Presents: The Great Eggscape! The Bad Seed Presents: The Good, the Bad, the Spooky! The Cool Bean Presents: As Cool as It Gets That's What Dinosaurs Do